A Systematic Literature Review: Entrepreneurship among University Students - Wanda Putra, Riki; Wardi, Yunia; Evanita, Susi; Sandi, Hendrik Heri (Yayasan Sinergi Kawula Muda, 2025)
This study aims to examine the latest developments in the study of entrepreneurship among university students with a special focus on entrepreneurial intention and entrepreneurship education. Using a Systematic Literature Review approach supported by bibliometric analysis, this study traces scientific articles published in the past year containing keywords such as entrepreneurship, entrepreneurial intention, entrepreneurship education, and student entrepreneurship. The visualization results show that entrepreneurial intention is the most dominant topic, which is closely connected to entrepreneurship education and entrepreneurship as the core of the literature review. Three main theme groups were also found: (1) psychological and personal themes such as gender and effectuation; (2) educational themes, such as emotional competencies and design education; and (3) technology and innovation themes, such as artificial intelligence and sustainability. The brighter colors of the technology keywords indicate that these issues are current research trends in the context of student entrepreneurship. This study concludes that the development of student entrepreneurship is not only influenced by internal factors such as motivation and emotional competencies, but also by innovative educational approaches and technology integration. These findings provide strategic direction for the development of a more adaptive and contextual entrepreneurship curriculum in the university environment.